Increased ATG5 Expression Predicts Poor Prognosis and Promotes EMT in Cervical Carcinoma - Zhou, Suna; Wang, Xuequan; Ding, Jiapei; Yang, Haihua; Xie, Youyou (Frontiers in Cell and Developmental Biology, 2021)
Cervical cancer is the second-highest incidence and mortality of female malignancy. The major causes of mortality in patients with cervical cancer are invasion and metastasis. Epithelial mesenchymal transition (EMT) process plays a major role in the acquisition of metastatic potential and motility. Autophagy related genes (ARGs) are implicated in EMT process, and autophagy exerts a dual function in EMT management at different phases of tumor progression. However, the role of specific ARGs during EMT process has not yet been reported in cervical cancer. Based on the data from the Cancer Genome Atlas (TCGA) cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC) sequencing database, we performed the prognosis analysis for those ARGs obtained from the Human Autophagy Database. ATG5 was identified as the only important harmful marker influencing on survival of cervical cancer patients by univariate Cox regression (HR 1.7; 95% CI: 1.0-2.8, p=0.047) and the 5 years survival rate for high and low ATG5 expression groups was 0.486(0.375-0.631) and 0.782(0.708-0.863) respectively. TCGA CESC methylation data showed that 8 methylation sites of ATG5 could also be significantly associated with the overall survival (OS) of cervical cancer patients. Single-sample gene-set enrichment and gene functional enrichment results showed that ATG5 was correlated with some cancer-related pathways, such as phagocytosis-related genes, endocytosis-related genes, immune-related genes, EMT score, and some EMT signature-related genes. Next, cell migration and invasion assay and western blot were applied to detect the function of ATG5 in EMT of cervical cancer. In cervical cancer cells, ATG5 knockdown resulted in attenuation of migration and invasion. The functional study showed that knockdown of ATG5 could reverse EMT process by P-ERK, P-NFκBp65, P-mTOR pathways, and so on. In conclusion, the present study implies that ATG5 was a major contributor to EMT regulation and poor prognosis in cervical cancer.